A PPS textile diaphragm cloth
By pretreatment of diluted sodium hyaluronate solution and post-treatment of sulfur fumigation on PPS fibers, high hydrophilicity and high airtightness PPS textile diaphragm fabrics were prepared, which solved the problems of unstable performance and poor hydrophilicity of the existing diaphragm fabrics, and achieved the preparation of diaphragm fabrics with excellent performance and low cost.
Patent Information
- Application Number
- CN202211314667.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-26
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2042-10-26
AI Technical Summary
The existing asbestos diaphragm cloth has unstable performance under high temperature and electrolyte, which is prone to expand and loose, and has environmental pollution problems. The polyphenylene sulfide fiber diaphragm cloth has poor hydrophilicity and cannot meet the use requirements.
PPS fiber pretreatment was performed using a sodium hyaluronate solution containing dilute nitric acid, and yarn was prepared by a spinning process of comb-striped-rod-rod-rod-winding-twisted-heat-setting, followed by a high-density woven fabric by a plain weaving and sulphur fumigation.
The prepared PPS textile diaphragm fabric has good hydrophilicity, high airtightness, easy preparation, excellent performance, low manufacturing cost, and is suitable for water electrolytic cells.
Smart Images

Figure CN115538006B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of electrolytic cell diaphragm cloth, and specifically discloses a PPS textile diaphragm cloth. Background Art
[0002] The electrolytic cell consists of a cell body, an anode and a cathode, and most of them use a diaphragm to separate the anode chamber from the cathode chamber. According to the different electrolytes, it can be divided into three categories: aqueous solution electrolytic cell, molten salt electrolytic cell and non-aqueous solution electrolytic cell. In a water electrolytic cell, when direct current passes through the electrolytic cell, an oxidation reaction occurs at the interface between the anode and the solution, and a reduction reaction occurs at the interface between the cathode and the solution to produce the desired product. Optimizing the design of the electrolytic cell structure and reasonably selecting the diaphragm material are the key to improving current efficiency, reducing cell voltage and saving energy consumption. When electrolyzing water, the electrolytes in the cathode and anode chambers are the same. The diaphragm of the electrolytic cell needs to separate the cathode and anode chambers to ensure the purity of hydrogen and oxygen and prevent explosion caused by mixing hydrogen and oxygen. The diaphragm is made of inert materials, such as the asbestos diaphragm used for a long time in the chlor-alkali industry. At present, the main domestic alkaline water electrolysis hydrogen production equipment manufacturers still use asbestos cloth as diaphragm, but the performance of asbestos diaphragm is unstable. When the brine contains calcium and magnesium impurities, hydroxide precipitation is easily generated in the diaphragm, reducing the permeability; under relatively high temperatures and the action of electrolyte, it will also swell and loosen, and asbestos also has the disadvantage of environmental pollution. In the prior art, diaphragm cloth made of polyphenylene sulfide fiber is often used to replace asbestos diaphragm cloth to solve the above problems. However, due to the defect of poor water absorption of polyphenylene sulfide fiber, the diaphragm cloth obtained has poor hydrophilicity and cannot meet the use requirements well. Therefore, it is necessary to further improve the polyphenylene sulfide fiber diaphragm cloth material. For example, CN111733602A discloses a method for preparing a PPS / MOFs micro-nano fiber alkaline water electrolyzer diaphragm, including preparing a PPS melt-blown cloth from a dried PPS resin through a melt-blown device; hydrophilically modifying the PPS melt-blown cloth; modifying the hydrophilically modified PPS melt-blown cloth with alkali-resistant hydrophilic MOFs; hot-pressing the MOFs-modified PPS melt-blown cloth, and rapidly cooling it to obtain a PPS / MOFs micro-nano fiber alkaline water electrolyzer diaphragm. The hydrophilic ZIF-90 modification method not only improves its hydrophilicity and alkali absorption rate, but also the three-dimensional pore structure of the MOFs materials possessed by ZIF-90 can effectively prevent the penetration of gas molecules. Although the diaphragm prepared by the above method has excellent performance and good hydrophilicity, its preparation process is complicated and requires the use of expensive materials for modification. It cannot be used for large-scale industrial application without reducing costs. CN107574525A discloses a blended diaphragm cloth for a water electrolyzer, which is a woven fabric or non-woven fabric formed by blended yarns of polyphenylene sulfide fiber and vinylon fiber, and has an average diameter of 0.1 to 15 μm; wherein the content of the polyphenylene sulfide fiber is 90 to 50% by weight, and the content of the vinylon fiber is 10 to 50% by weight, and the prepared diaphragm cloth has excellent wettability and ion permeability to alkali liquid during use. However, vinylon fiber is not resistant to hot water, has poor elasticity, and has a poor life in hot water, which affects the performance of the final blended diaphragm cloth and limits the application of the above preparation method.At present, there is a need to find a polyphenylene sulfide fiber diaphragm cloth which is easy to prepare, has excellent performance and low manufacturing cost. Summary of the invention
[0003] In view of the above situation, the present invention discloses a PPS textile diaphragm cloth with good hydrophilicity, high air tightness, convenient preparation, excellent performance and low manufacturing cost.
[0004] The technical solution of the present invention is as follows:
[0005] A PPS textile diaphragm cloth is prepared by the following steps:
[0006] 1) PPS fiber pretreatment: First, the pure PPS fiber was immersed in a sodium hyaluronate solution containing dilute nitric acid for 2-4 hours; then, it was taken out and washed with deionized water and dried;
[0007] 2) Spinning: The yarn is obtained by spinning through the spinning process of carding-drawing-roving-spinning-winding-doubling-twisting-heat setting;
[0008] 3) Weaving: The obtained yarn is woven through a plain loom to obtain a high-density woven fabric with a warp density of 40 to 80 strands / inch and a weft density of 35 to 70 strands / inch as a diaphragm cloth;
[0009] 4) Post-treatment: placing the diaphragm cloth prepared in step 3) in a closed room and post-treating the diaphragm cloth using sulfur fumigation.
[0010] Furthermore, in the above-mentioned PPS textile diaphragm cloth, the sodium hyaluronate solution containing dilute nitric acid in step 1) is prepared by the following steps: adding 1 part of a 14-23% dilute nitric acid aqueous solution to 1-4 parts of a sodium hyaluronate solution at a temperature of 10-30°C, and stirring at 40-200rpm / min.
[0011] Furthermore, in the above-mentioned PPS textile diaphragm cloth, the sodium hyaluronate solution is prepared by the following steps:
[0012] a. By weight, add 1 part of sodium hyaluronate dry powder to 9 parts of an aqueous solution containing 0.005-0.01 parts of hyaluronidase, and perform enzymolysis at 30-35° C. for 10-20 minutes to obtain 10 parts of hyaluronic acid enzymolysis solution;
[0013] b. Add the hyaluronic acid enzymatic hydrolysis solution obtained in step a to an arginine solution having a concentration of 50-120 g / L, wherein the volume ratio of the hyaluronic acid enzymatic hydrolysis solution to the arginine solution is 1:1-4; after the addition is completed, stir at 30-35° C. for 1-4 hours to obtain a mixed solution A;
[0014] c. Mix the mixed solution A and PEG20000 in a mass ratio of 5-10:1, add triethanolamine to adjust the pH of the system to between 6 and 7, and let it stand for 2-6 hours to obtain a sodium hyaluronate solution.
[0015] Furthermore, in the above-mentioned PPS textile diaphragm cloth, the diameter of the PPS fibers in the PPS textile diaphragm cloth is 0.5-5 μm.
[0016] Furthermore, in the above-mentioned PPS textile diaphragm cloth, the cross section of the PPS fibers in the PPS textile diaphragm cloth is cross-shaped.
[0017] Furthermore, in the above-mentioned PPS textile diaphragm cloth, the warp twist coefficient of the yarn prepared in step 2) is 4.2-4.5, and the weft twist coefficient is 1.6-2.2.
[0018] Furthermore, in the above-mentioned PPS textile diaphragm cloth, in step 4), the parameters of the sulfur fumigation treatment are: temperature 40-65°C, fumigation time 4-8h, sulfur dosage 10-20g / m 3 .
[0019] Furthermore, the water absorption speed of the above-mentioned PPS textile diaphragm cloth is less than 8s.
[0020] Furthermore, the above-mentioned PPS textile diaphragm cloth has a thickness of 0.1-0.8 mm, an air tightness of 250-900 mmH2O, and a surface resistance of 35-50 Ω.cm 2 .
[0021] The air tightness of the blended diaphragm cloth of the present invention is 250-900 mmH2O. Under the condition of keeping airtight for 2 minutes under the pressure of 200 mm or more H2O, it can basically meet the air tightness use requirements of the diaphragm cloth in the actual water electrolyzer, and at the same time take into account that the diaphragm cloth can have excellent air tightness, ion passage efficiency and processability of the diaphragm cloth. If the air tightness is less than 200 mmH2O pressure, the basic requirements of the diaphragm cannot be met, and the purity of the generated gas is affected; if the air tightness is higher than 900 mmH2O pressure, on the one hand, it is difficult to weave and the cost is high, and on the other hand, it will increase the resistance of the diaphragm, thereby increasing the energy consumption per unit gas production. The thickness of the diaphragm cloth for the water electrolyzer of the present invention is preferably 0.4-0.6 mm, and the air tightness is preferably 300-400 mmH2O pressure.
[0022] Furthermore, the above-mentioned PPS textile diaphragm cloth is used in a water electrolyzer.
[0023] The present invention has the following beneficial effects:
[0024] The present invention uses a sodium hyaluronate solution containing dilute nitric acid for pretreatment. Compared with strong acid treatment, the conditions are mild, the environmental pollution is small, and the fiber has good hydrophilicity; and the present invention has a small twist during the spinning process, the yarn hairiness is plump and fluffy, the air tightness is improved, and the air permeability is reduced. Finally, in the post-treatment of the diaphragm cloth, sulfur treatment is used to further increase the hydrophilicity of the diaphragm cloth and extend its life. In summary, the PPS diaphragm cloth prepared by this method has good hydrophilicity and a water absorption rate of less than 8s. The fast water absorption rate reflects the excellent hydrophilicity of the diaphragm cloth. The diaphragm cloth has good hydrophilicity, which can increase ion permeability during use, reduce energy consumption, and reduce production costs; in addition, due to the good hydrophilicity of the diaphragm, a layer of water film can be formed on the surface of the diaphragm during use, so that the pore size of the diaphragm is reduced, thereby effectively preventing the generated hydrogen and oxygen from passing through each other, so that the purity of hydrogen and oxygen is increased. The present invention is convenient to prepare, has mild preparation conditions, and has low preparation cost, and is particularly suitable for water electrolyzers. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 It is a performance comparison diagram of the air tightness of the embodiments;
[0026] Figure 2 It is a performance comparison diagram of water absorption of the embodiments;
[0027] Figure 3 It is a comparison chart of water absorption speed of the examples. DETAILED DESCRIPTION
[0028] A PPS textile diaphragm cloth is prepared by the following steps:
[0029] 1) PPS fiber pretreatment: First, the pure PPS fiber was immersed in a sodium hyaluronate solution containing dilute nitric acid for 2-4 hours; then, it was taken out and washed with deionized water and dried;
[0030] 2) Spinning: The yarn with low twist is obtained by spinning through the spinning process of carding-drawing-roving-spinning-winding-doubling-twisting-heat setting;
[0031] 3) Weaving: The obtained yarn is woven through a plain loom to obtain a high-density woven fabric with a warp density of 40 to 80 strands / inch and a weft density of 35 to 70 strands / inch as a diaphragm cloth;
[0032] 4) Post-treatment: placing the diaphragm cloth prepared in step 3) in a closed room and post-treating the diaphragm cloth using sulfur fumigation.
[0033] The sodium hyaluronate solution containing dilute nitric acid in step 1) is prepared by the following steps:
[0034] At a temperature of 10-30° C., add 1 part of a 14-23% dilute nitric acid aqueous solution to 1-4 parts of a sodium hyaluronate solution and stir at 40-200 rpm / min.
[0035] The sodium hyaluronate solution is prepared by the following steps:
[0036] a. By weight, add 1 part of sodium hyaluronate dry powder to 9 parts of an aqueous solution containing 0.005-0.01 parts of hyaluronidase, and perform enzymolysis at 30-35° C. for 10-20 minutes to obtain 10 parts of hyaluronic acid enzymolysis solution;
[0037] b. Add the hyaluronic acid enzymatic hydrolysis solution obtained in step a to an arginine solution having a concentration of 50-120 g / L, wherein the volume ratio of the hyaluronic acid enzymatic hydrolysis solution to the arginine solution is 1:1-4; after the addition is completed, stir at 30-35° C. for 1-4 hours to obtain a mixed solution A;
[0038] c. Mix the mixed solution A and PEG20000 in a mass ratio of 5-10:1, add triethanolamine to adjust the pH of the system to between 6 and 7, and let it stand for 2-6 hours to obtain a sodium hyaluronate solution.
[0039] The diameter of the PPS fibers in the PPS textile diaphragm cloth is 0.5-5 μm.
[0040] The cross section of the PPS fiber in the PPS textile diaphragm cloth is cross-shaped.
[0041] The warp twist coefficient of the yarn prepared in step 2) is 1.4 to 1.9, and the weft twist coefficient is 1.6 to 2.2.
[0042] In step 4), the parameters of sulfur fumigation treatment are: temperature 40-65°C, fumigation time 4-8h, sulfur dosage 10-20g / m 3 .
[0043] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0044] The PPS fiber of the present invention was purchased from Zhejiang Xinhecheng Special Materials Co., Ltd. Model 2D*51mm
[0045] Sodium hyaluronate was purchased from MACKLIN, item number H832247
[0046] Hyaluronidase was purchased from Aladdin Reagent Network, item number H141272-250mg
[0047] The reagents or instruments used in the examples of the present invention without indicating the manufacturer are all conventional reagent products that can be obtained through commercial purchase.
[0048] Example 1
[0049] A PPS textile diaphragm cloth is prepared by the following steps:
[0050] 1) PPS fiber pretreatment: First, the pure PPS fiber was immersed in a sodium hyaluronate solution containing dilute nitric acid for 2 h; then, it was taken out and washed with deionized water and dried;
[0051] 2) Spinning: The yarn with low twist is obtained by spinning through the spinning process of carding-drawing-roving-spinning-winding-doubling-twisting-heat setting;
[0052] 3) Weaving: The obtained yarn is woven through a plain loom to obtain a high-density woven fabric with a warp density of 40 strands / inch and a weft density of 35 strands / inch as a diaphragm cloth;
[0053] 4) Post-treatment: placing the diaphragm cloth prepared in step 3) in a closed room and post-treating the diaphragm cloth using sulfur fumigation.
[0054] The sodium hyaluronate solution containing dilute nitric acid in step 1) is prepared by the following steps:
[0055] At 10°C, add 1 part of 14% diluted nitric acid aqueous solution to 1 part of sodium hyaluronate solution and stir at 40 rpm / min.
[0056] The sodium hyaluronate solution is prepared by the following steps:
[0057] a. By weight, add 1 part of sodium hyaluronate dry powder to 9 parts of an aqueous solution containing 0.005 parts of hyaluronidase, and perform enzymolysis at 30° C. for 10 minutes to obtain 10 parts of hyaluronic acid enzymolysis solution;
[0058] b. Add the hyaluronic acid enzymatic hydrolysis solution obtained in step a to the arginine solution with a concentration of 50 g / L, and the volume ratio of the hyaluronic acid enzymatic hydrolysis solution to the arginine solution is 1:1; after the addition is completed, stir at 30° C. for 1 hour to obtain a mixed solution A;
[0059] c. Mix the mixed solution A and PEG20000 in a mass ratio of 10:1, add triethanolamine to adjust the pH of the system to between 6 and 7, and let it stand for 2 hours to obtain a sodium hyaluronate solution.
[0060] The average diameter of the PPS fibers in the PPS woven diaphragm cloth is 0.5 μm.
[0061] The cross section of the PPS fiber in the PPS textile diaphragm cloth is cross-shaped.
[0062] The warp twist coefficient of the yarn prepared in step 2) is 1.4 to 1.9, and the weft twist coefficient is 1.6 to 2.2.
[0063] In step 4), the parameters of sulfur fumigation treatment are: temperature 40°C, fumigation time 4h, sulfur dosage 10g / m 3 .
[0064] The thickness of the diaphragm cloth is 0.5 mm.
[0065] Example 2
[0066] A PPS textile diaphragm cloth is prepared by the following steps:
[0067] 1) PPS fiber pretreatment: First, the pure PPS fiber was immersed in a sodium hyaluronate solution containing dilute nitric acid for 4 hours; then, it was taken out and washed with deionized water and dried;
[0068] 2) Spinning: The yarn with low twist is obtained by spinning through the spinning process of carding-drawing-roving-spinning-winding-doubling-twisting-heat setting;
[0069] 3) Weaving: The obtained yarn is woven through a plain loom to obtain a high-density woven fabric with a warp density of 60 strands / inch and a weft density of 50 strands / inch as a diaphragm cloth;
[0070] 4) Post-treatment: placing the diaphragm cloth prepared in step 3) in a closed room and post-treating the diaphragm cloth using sulfur fumigation.
[0071] The sodium hyaluronate solution containing dilute nitric acid in step 1) is prepared by the following steps:
[0072] At 20°C, add 1 part of 19% diluted nitric acid aqueous solution to 2 parts of sodium hyaluronate solution and stir at 100 rpm / min.
[0073] The sodium hyaluronate solution is prepared by the following steps:
[0074] a. By weight, add 1 part of sodium hyaluronate dry powder to 9 parts of an aqueous solution containing 0.075 parts of hyaluronidase, and perform enzymolysis at 33° C. for 15 minutes to obtain 10 parts of hyaluronic acid enzymolysis solution;
[0075] b. Add the hyaluronic acid enzymatic hydrolysis solution obtained in step a to the arginine solution with a concentration of 90 g / L, and the volume ratio of the hyaluronic acid enzymatic hydrolysis solution to the arginine solution is 1:2; after the addition is completed, stir at 33° C. for 1-4 hours to obtain a mixed solution A;
[0076] c. Mix the mixed solution A and PEG20000 in a mass ratio of 7:1, add triethanolamine to adjust the pH of the system to between 6 and 7, and let it stand for 4 hours to obtain a sodium hyaluronate solution.
[0077] The average diameter of the PPS fibers in the PPS woven diaphragm cloth is 2 μm.
[0078] The cross section of the PPS fiber in the PPS textile diaphragm cloth is cross-shaped.
[0079] The warp twist coefficient of the yarn prepared in step 2) is 1.4 to 1.9, and the weft twist coefficient is 1.6 to 2.2.
[0080] In step 4), the parameters of sulfur fumigation treatment are: temperature 50°C, fumigation time 6h, sulfur dosage 15g / m 3 .
[0081] The thickness of the diaphragm cloth is 0.5 mm.
[0082] Example 3
[0083] A PPS textile diaphragm cloth is prepared by the following steps:
[0084] 1) PPS fiber pretreatment: First, the pure PPS fiber was immersed in a sodium hyaluronate solution containing dilute nitric acid for 2-4 hours; then, it was taken out and washed with deionized water and dried;
[0085] 2) Spinning: The yarn with low twist is obtained by spinning through the spinning process of carding-drawing-roving-spinning-winding-doubling-twisting-heat setting;
[0086] 3) Weaving: The obtained yarn is woven through a plain loom to obtain a high-density woven fabric with a warp density of 80 strands / inch and a weft density of 70 strands / inch as a diaphragm cloth;
[0087] 4) Post-treatment: placing the diaphragm cloth prepared in step 3) in a closed room and post-treating the diaphragm cloth using sulfur fumigation.
[0088] The sodium hyaluronate solution containing dilute nitric acid in step 1) is prepared by the following steps:
[0089] At 30°C, add 1 part of 23% dilute nitric acid aqueous solution to 4 parts of sodium hyaluronate solution and stir at 200 rpm / min.
[0090] The sodium hyaluronate solution is prepared by the following steps:
[0091] a. By weight, add 1 part of sodium hyaluronate dry powder to 9 parts of an aqueous solution containing 0.01 parts of hyaluronidase, and perform enzymolysis at 35° C. for 20 minutes to obtain 10 parts of hyaluronic acid enzymolysis solution;
[0092] b. Adding the hyaluronic acid enzymatic hydrolysis solution obtained in step a to the arginine solution with a concentration of 120 g / L, the volume ratio of the hyaluronic acid enzymatic hydrolysis solution to the arginine solution finally added is 1:4; after the addition is completed, stirring at 335° C. for 4 hours to obtain a mixed solution A;
[0093] c. Mix the mixed solution A and PEG20000 in a mass ratio of 5:1, add triethanolamine to adjust the pH of the system to between 6 and 7, and let it stand for 6 hours to obtain a sodium hyaluronate solution.
[0094] The average diameter of the PPS fibers in the PPS woven diaphragm cloth is 5 μm.
[0095] The cross section of the PPS fiber in the PPS textile diaphragm cloth is cross-shaped.
[0096] The warp twist coefficient of the yarn prepared in step 2) is 1.4 to 1.9, and the weft twist coefficient is 1.6 to 2.2.
[0097] In step 4), the parameters of the sulfur fumigation treatment are: temperature 65°C, fumigation time 8h, sulfur dosage 20g / m 3 .
[0098] The thickness of the diaphragm cloth is 0.5 mm.
[0099] Comparative Example 1
[0100] Comparative Example
[0101] The 1) PPS fiber pretreatment described in Example 2 is not included, and the rest is the same as Example 2.
[0102] Comparative Example 2
[0103] Comparative Example
[0104] The yarn prepared in step 2) has a high twist, the warp twist coefficient is 3.4-4.1, the weft twist coefficient is 2.6-3.2, and the rest is the same as in Example 2.
[0105] Comparative Example 3
[0106] Comparative Example
[0107] The post-treatment step 4) is not included, and the rest is the same as in Example 2.
[0108] Test Case
[0109] The performance tests were conducted on the diaphragm cloths produced in Examples 1-3 and Comparative Examples 1-3. The test items and methods are as follows:
[0110]
Air tightness
[0111] According to the Chinese building materials industry standard JCT 211-2009 "Diaphragm Asbestos Cloth" standard, 4.5.2 Airtightness Test
[0112]
Water absorption rate
[0113] The water absorption rate before and after hydrophilic treatment was tested according to GB / T21655.1-2008 standard.
[0114]
Surface resistance
[0115] According to the test standard of the electronic industry standard SJ / T 10171.5-91 of the People's Republic of China for the surface resistance of alkaline battery diaphragms, the equipment for testing the surface resistance of PPS diaphragms is set up, and the setting parameters of the equipment are as follows:
[0116]
Water absorption speed
[0117] The test was conducted according to 7.1.1 dripping method in JIS L1907-2010 Test method for water absorption of fiber products.
[0118] The results are shown in Table 1 and Appendix Figure 1-3
[0119] Table 1 PPS textile diaphragm cloth performance test
[0120]
[0121] From Table 1 and Appendix Figure 1-3 It can be seen from the data that the pretreatment process and the post-treatment process in the process of the present invention can improve the hydrophilicity of the PPS textile diaphragm cloth well, and do not affect the air tightness of the textile diaphragm cloth. Although the PPS textile diaphragm cloth without pretreatment or post-treatment has good air tightness, it has poor hydrophilicity. The air tightness of the embodiment using light twist is much better than that of the comparative example 2 using no light twist. It can be concluded that the PPS diaphragm cloth prepared by this method has good hydrophilicity and high air tightness.
[0122] After testing, the diaphragm cloth prepared in Example 2 can be used for 1-3 years at a temperature of 95-130°C; the diaphragm is under a pressure of 0-4.0KPa, and the diaphragm cloth has an airtightness of 250-900 mm water column pressure, and no bubbles are generated within 2 minutes.
[0123] The above-mentioned embodiments only express a limited number of preferred implementations of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.
Claims
1. A PPS textile diaphragm cloth, characterized in that: The preparation method is as follows: 1) PPS fiber pretreatment: first, the pure PPS fiber is immersed in a sodium hyaluronate solution containing dilute nitric acid for pretreatment for 2-4 hours; after being taken out, it is subsequently washed with deionized water and dried; 2) Spinning: the yarn is spun through a spinning process of carding-drawing-roving-spinning-winding-doubling-twisting-heat setting to obtain yarn; 3) Weaving: the obtained yarn is woven through a plain loom to obtain a warp density of 40 to 80 strands / inch and a weft density of 35 to 7 0 strands / inch high-density woven fabric as the diaphragm cloth; 4) post-treatment: placing in a closed room, using sulfur fumigation to post-treat the diaphragm cloth prepared in step 3), wherein the sodium hyaluronate solution containing dilute nitric acid in step 1) is prepared by the following steps: at a temperature of 10-30°C, 1 part of a 14-23% dilute nitric acid aqueous solution is added to 1-4 parts of a sodium hyaluronate solution, and stirred at 40-200rpm, wherein the sodium hyaluronate solution is prepared by the following steps: a. by weight, 1 part of sodium hyaluronate dry powder is added to 9 parts of aqueous solution containing 0.005-0.01 parts of hyaluronidase, and enzymolysis is carried out at 30-35°C for 10-20 minutes to obtain 10 parts of hyaluronic acid enzymolysis solution; b. The hyaluronic acid enzymolysis solution obtained in step a is added to an arginine solution with a concentration of 50-120g / L, and the volume ratio of the hyaluronic acid enzymolysis solution to the arginine solution is 1:1-4; after the addition is completed, stir at 30-35°C for 1-4h to obtain a mixed solution A; c. Mix the mixed solution A and PEG20000 in a mass ratio of 5-10:1, add triethanolamine to adjust the pH of the system to between 6 and 7, and let it stand for 2-6 hours to obtain a sodium hyaluronate solution. The diameter of the PPS fiber in the PPS textile diaphragm cloth is 0.5-5 μm, and the cross-section of the PPS fiber in the PPS textile diaphragm cloth is cross-shaped. The warp twist coefficient of the yarn prepared in the step 2) is 4.2-4.5, and the weft twist coefficient is 1.6-2.
2.
2. A PPS textile diaphragm cloth according to claim 1, characterized in that: In step 4), the parameters of the sulfur fumigation treatment are: temperature 40-65° C., fumigation time 4-8 hours, and sulfur dosage 10-20 g / m3.
3. A PPS textile diaphragm cloth according to claim 1, characterized in that: The water absorption speed of the diaphragm cloth is less than 8s.
4. A PPS textile diaphragm cloth according to claim 1, characterized in that: The thickness of the diaphragm cloth is 0.1-0.8 mm, the air tightness is 250-900 mmH2O, and the surface resistance is 35-50 Ω / cm2.
5. Use of the PPS textile diaphragm cloth according to any one of claims 1 to 4 in a water electrolyzer.
Citation Information
Patent Citations
Preparation method of PPS / MOFs micro-nano fiber alkaline water electrolytic cell diaphragm
CN111733602A
Blending diaphragm cloth used for water electrolyser
CN107574525A
Preparation method of super-hydrophilic PPS composite fiber membrane
CN112252022A